Beyond market failures: The market creating and shaping roles of state investment banks - Mariana Mazzucato; Caetano C. R. Penna (Levy Economics Institute of Bard College, 2015)
Recent decades witnessed a trend whereby private markets retreated from financing the real economy, while, simultaneously, the real economy itself became increasingly financialized. This trend resulted in public finance becoming more important for investments in capital development, technical change, and innovation. Within this context, this paper focuses on the roles played by a particular source of public finance: state investment banks (SIBs). It develops a conceptual typology of the different roles that SIBs play in the economy, which together show the market creation/shaping process of SIBs rather than their mere "market fixing" roles. This paper discusses four types of investments, both theoretically and empirically: countercyclical, developmental, venture capitalist, and challenge led. To develop the typology, we first discuss how standard market failure theory justifies the roles of SIBs, the diagnostics and evaluation toolbox associated with it, and resulting criticisms centered on notions of "government failures." We then show the limitations of this approach based on insights from Keynes, Schumpeter, Minsky, and Polanyi, as well as other authors from the evolutionary economics tradition, which help us move toward a framework for public investments that is more about market creating/shaping than market fixing. As frameworks lead to evaluation tools, we use this new lens to discuss the increasingly targeted investments that SIBs are making, and to shed new light on the usual criticisms that are made about such directed activity (e.g., crowding out and picking winners). The paper ends with a proposal of directions for future research.
Keywords: G20; L52; O16; O38; P16; 330; Development Banking; Market Failure; Mission-oriented Finance; Public Finance; State Investment Banks